Moisture migration as an influencing factor in food freshness biocomposite packaging: A trend analysis review - Mohamad Khairul Aiman, Mohd Fauzi; Okwuwa, Chigozie Charity; Nor Hanuni, Ramli; Azren, Aida Asmawi; Jose, Rajan; Fatmawati, Adam (Elsevier Ltd, 2025)
Global demand for fresh and high-quality food increased at this modern age to satisfy on quality requirement. Water moisture is majority affected the quality of a fresh food. This work analysed the connection of water effect in particular migration and key concern on the food packaging research systematically and bibliometrically. Scopus journal databases in the last 45 years were evaluated using VOSviewer version (1.6.20) on the global trend of journal, institution and countries of the published literatures. The key point and highlight is food packaging material or biocomposite for moisture control. The finding revealed that active food packaging, tensile strength, water moisture and activity are the top co-occurrence keywords. The cluster of Natural Biodegradable Film for Food Packaging being the most popular of publication attention. The International Journal of Biological Macromolecules identified as most influential journal. China is the leading country in this key area. Also, chitosan and cellulose biomaterials incorporated with co-polymer and active compound is the primary interest for active food packaging to control water from activate the pathogens and microbes activities. This review is a valuable reference for future food packaging which specifically focus on moisture migration. Suitable biomaterial which able to lower water migration and activities is important to keep food fresh and remains its quality.